EVALUASI TAMAN PEMULIHAN GIZI TERHADAP PERILAKU IBU BALITA GIZI BURUK DAN GIZI KURANG DI PUSKESMAS JATIWATES KABUPATEN JOMBANG: Evaluation Of Nutrition Recovery Park On Mother Behavior Of Bad Nutrition And Less Nutrition In Jatiwates, Jombang - Ningtyas, Septi Fitrah; Grah Prihartanti, Niken; Mudhawaroh, Mudhawaroh; Ratnawati, Mamik (LPPM - STIKES Pemkab Jombang, 2021)
Introduction: The problem of malnutrition is one of the problems that often becomes a controversy in the territory of Indonesia. The purpose of this study was to analyze the Nutrition Recovery Park (NRP) program on the nutritional status of children in Jatiwates, Jombang. Method: This study used an observational analytic method with a retrospective cohort study design. The population in this study were all mothers of children under five who had malnourished toddlers in the work area of ??Jatiwates Health Center with 36 respondents. The sampling technique uses total sampling. Data analysis using chi square statistical test, followed by logistic regression test. Results: The results of the statistical test showed a significant relationship between the behavior of mothers towards the nutritional status of children while the knowledge and attitudes of mothers were not significantly related to nutritional status. Conclusion: The NRP program is also very helpful for mothers in improving the nutritional status of children, in NRP mothers will better understand the nutritional needs of children, and how to process food properly and correctly, which indirectly the mother's actions will continue the NRP program at home